Clustering and jamming in epithelial–mesenchymal co-cultures. Issue 40 (21st September 2016) - Gamboa Castro, Marielena; Leggett, Susan E.; Wong, Ian Y.
Abstract : Binary mixtures of mammalian cells self-organize into multicellular clusters that coarsen above a critical cell density. Abstract : Collective behaviors emerge from coordinated cell–cell interactions during the morphogenesis of tissues and tumors. For instance, cells may display density-dependent phase transitions from a fluid-like "unjammed" phase to a solid-like "jammed" phase, while different cell types can "self-sort". Here, we comprehensively track single cell dynamics in mixtures of sheet-forming epithelial cells and dispersed mesenchymal cells. We find that proliferating epithelial cells nucleate multicellular clusters that coarsen at a critical density, arresting migration and strengthening spatial velocity correlations. The addition of mesenchymal cells can slow cluster formation and coarsening, resulting in more dispersed individual cells with weak spatial velocity correlations. These behaviors have analogies with a jamming–unjamming transition, where the control parameters are cell density and mesenchymal fraction. This complex interplay of proliferation, clustering and correlated migration may have physical implications for understanding epithelial–mesenchymal interactions in development and disease.